Urban–rural environmental exposure during childhood and subsequent risk of inflammatory bowel disease: a meta-analysis. (3rd June 2019) - Song, Conghua; Yang, Jinpu; Ye, Wen; Zhang, Yuting; Tang, Chunyan; Li, Xiaomei; Zhou, Xiaojiang; Xie, Yong
ABSTRACT: Background : The relationship between living conditions in urban and rural areas during childhood and subsequent inflammatory bowel disease (IBD) remains controversial. Aim : To explore the association between environmental exposures early in life and the subsequent risk of IBD. Methods : Literature searches were conducted in the following databases: PubMed, EMBASE, and Conference Proceedings Citation Index. Studies were analyzed separately using rate ratios (RRs) or odds ratios (ORs) with 95% confidence intervals. Results : The search strategy identified 15 studies. Of these, 9 studies explored the association between urban exposure during childhood and ulcerative colitis (UC), and 12 and 4 studies explored this relationship with Crohn's disease (CD) and IBD, respectively. A meta-analysis showed that the pooled ORs estimated for the case–control studies of UC, CD, and IBD were 1.16 (0.83, 1.61), 1.45 (1.45, 1.85), and 1.34 (1.11, 1.62), respectively. The pooled RR estimated for the cohort studies of CD and IBD was 1.48 (1.17, 1.87). The stratified analysis and meta-regression showed significant relationships between CD and living conditions in case–control studies published during 2010–2017 and in non-European countries ( P  < 0.05). Conclusions : Living conditions during childhood are positively associated with the subsequent development of IBD. Urban living environment is more common among those with CD than UC.